Donor transparency and aid allocation - Jörg Faust (Deutsches Institut für Entwicklungspolitik (DIE), 2011)
In recent years, the transparency of foreign aid has received substantial attention among aid practitioners. This analysis shows the impact of political transparency in donor countries on those countries' formal promotion of aid transparency and on their concrete aid allocation patterns. Political transparency as measured by standard corruption indices not only impacts on the engagement of bilateral donors in the International Aid Transparency Initiative. Differences in political transparency in donor countries also explain a large part of their varying aid selectivity patterns. Donors with higher levels of political transparency allocate aid more according to recipients' neediness and institutional performance.
Keywords: 330